An Integrated Built-In Test and Repair Approach for Memories with 2D Redundancy - Oehler, Philipp; Hellebrand, Sybille; Wunderlich, Hans-Joachim (12th IEEE European Test Symposium (ETS'07))

Testing and Monitoring Nanoscale Systems - Challenges and Strategies for Advanced Quality Assurance - Hellebrand, Sybille; G. Zoellin, Christian; Wunderlich, Hans-Joachim; Ludwig, Stefan; Coym, Torsten; Straube, Bernd (43rd International Conference on Microelectronics, Devices and Material with the Workshop on Electronic Testing (MIDEM'07), (Invited Paper))

Testing and Monitoring Nanoscale Systems - Challenges and Strategies for Advanced Quality Assurance - Hellebrand, Sybille; G. Zoellin, Christian; Wunderlich, Hans-Joachim; Ludwig, Stefan; Coym, Torsten; Straube, Bernd (Informacije MIDEM, Ljubljana (Invited Paper))

An Efficient Fault Tolerant Mechanism to Deal with Permanent and Transient Failures in a Network on Chip - Ali, Muhammad; Hessler, Sven; Welzl, Michael; Hellebrand, Sybille (International Journal on High Performance Systems Architecture)

A Fault Tolerant Mechanism for Handling Permanent and Transient Failures in a Network on Chip - Ali, Muhammad; Welzl, Michael; Hessler, Sven; Hellebrand, Sybille (4th International Conference on Information Technology: New Generations (ITNG'07))

Test und Zuverlässigkeit nanoelektronischer Systeme - Becker, Bernd; Polian, Ilia; Hellebrand, Sybille; Straube, Bernd; Wunderlich, Hans-Joachim (1. GMM/GI/ITG-Fachtagung "Zuverlässigkeit und Entwurf")

Bildlichkeit und Bildkonzepte beim späten Herder - van Laak, Lothar (Der frühe und der späte Herder. Kontinuität und/oder Korrektur? Beiträge zur Konferenz der Internationalen Herder Gesellschaft Saarbrücken 2004)

Gutes Deuten, schlechtes Deuten. Das Prinzip der hermeneutischen Billigkeit - van Laak, Lothar (Ethik des Verstehens. Beiträge zur philosophischen und literarischen Hermeneutik)

Nachahmung nach der Nachahmungsästhetik – Mimesis und Präsenz bei Karl Philipp Moritz - van Laak, Lothar (Mediale Gegenwärtigkeit)

Einleitung zum Sammelband - van Laak, Lothar; Kaul, Susanne (Ethik des Verstehens. Beiträge zur philosophischen und literarischen Hermeneutik)

Uwe Johnsons Jahrestage als episches Erzählen der Moderne? Überlegungen im Anschluss an zwei Neuerscheinungen zum Erzählen in der Moderne und bei Uwe Johnson - van Laak, Lothar (Johnson-Jahrbuch 14)

“Ihr kennt die deutsche Seele nicht.” Geschichtskonzeption und filmischer Mythos in Fritz Langs Nibelungen - van Laak, Lothar (Antike und Mittelalter im Film. Konstruktion – Dokumentation – Projektion)

Ethik des Verstehens. Beiträge zur philosophischen und literarischen Hermeneutik

„Sängerpolemik und literarischer Selbstbezug in der Sangspruchdichtung: Aspekte der Streitkommunikation“ - Egidi, Margreth (ZfdPh 126)

Jean Piaget zur Einführung - Scharlau, Ingrid

Control of Attention by Nonconscious Information: Do Intentions Play a Role? - Scharlau, Ingrid (The 5th International Conference on Computer Vision Systems)
The present study explores the deployment of attention towards nonconscious information. It is both theoretically and empirically likely that the deployment of attention can be controlled by information which is not consciously registered (attentional priming), similar to the control of sensorimotor responses by nonconscious information (response priming). However, not much is known about the functional basis of attentional priming. The present experiment explore whether and how strongly intentions (current action pans) determine whether attention is allocated towards invisible information (so called direct parameter specification). The results demonstrate that intention-mediated control is possible, but it seems to break down easily, that is to provide a weak and non-robust type of control.
Keywords: visuo-spatial attention; metacontrast; masking; intention; direct parameter specification; perceptual latency; priming

Temporal processes in prime-mask interaction: Assessing perceptual consequences of masked information. - Scharlau, Ingrid (Advances in Cognitive Psychology)
Visual backward masking is frequently used to study the temporal dynamics of visual perception. These dynamics may include the temporal features of conscious percepts, as suggested, for instance, by the asynchronous-updating model (Neumann, 1982) and perceptual-retouch theory (Bachmann, 1994). These models predict that the perceptual latency of a visual backward mask is shorter than that of a like reference stimulus that was not preceded by a masked stimulus. The prediction has been confirmed by studies using temporal-order judgments: For certain asynchronies between mask and reference stimulus, temporal-order reversals are quite frequent (e.g. Scharlau, & Neumann, 2003a). However, it may be argued that these reversals were due to a response bias in favour of the mask rather than true temporal-perceptual effects. I introduce two measures for assessing latency effects that (1) are not prone to such a response bias, (2) allow to quantify the latency gain, and (3) extend the perceptual e
Keywords: temporal processes; prime mask interaction; perceptual consequences; masked information; visual backward masking; visual perception; Temporal Lobe; Visual Masking; Visual Perception; Consequence

Experiments on the Fehrer-Raab effect and the 'Weather Station Model' of visual backward masking. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The Fehrer-Raab effect (simple reaction time is unaffected by metacontrast masking of the test stimulus) seems to imply that a stimulus can trigger a voluntary reaction without reaching a conscious representation. However, it is also possible that the mask triggers the reaction, and that the masked test stimulus causes a focussing of attention from which processing of the mask profits, thus reaching conscious representation earlier. This is predicted by the Weather Station Model of visual masking. Three experiments tested this explanation. Experiment 1 showed that the masked test stimulus caused a temporal shift of the mask. Experiment 2 showed that the reaction in the Fehrer-Raab effect was not exclusively triggered by a conscious representation of the test stimulus: the mask was involved in evoking the reaction. Experiment 3 again revealed a temporal shift of the mask. However, the shift was only about half as large as the Fehrer-Raab effect. The psychometric functions suggested tha
Keywords: Fehrer-Raab effect; Weather Station Model; visual backward masking; reaction time; metacontrast masking; conscious representation; Cognition; Humans; Perceptual Masking; Pilot Projects; Psychology; Experimental; Psychometrics; Reaction Time; Visual Perception; Models; Reaction Time; Visual Contrast; Visual Masking

Visual attention and the mechanism of metacontrast. - Neumann, Odmar; Scharlau, Ingrid (Psychological Research)
The U-shaped metacontrast function may result from the superimposition of two monotonic components which reflect the effects of mechanisms similar to the peripheral and central processes suggested for backward pattern masking by Turvey (Psychol Rev 80:1-52, 1973). In an experiment using the disc-ring paradigm, it was demonstrated that the decreasing and increasing branches of the metacontrast function are differently affected by the exposure duration of the mask and a task-irrelevant stimulus (distractor) appearing in the contralateral visual hemifield. The phenomenal representation of masking is different for the two parts of the curve. It is suggested that masking in the second part of the masking function, but not in the first, is related to the control of visual attention. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: visual attention; metacontrast; backward pattern masking; monotonic components superimposition; Attention; Contrast Sensitivity; Humans; Judgment; Perceptual Masking; Visual Perception; Metacognition; Visual Contrast; Visual Attention; Visual Masking

Perceptual latency priming: A measure of attentional facilitation. - Scharlau, Ingrid (Psychological Research)
The present paper reviews recent research on perceptual latency priming (PLP). PLP is the relative latency advantage--earlier perception--of a visual stimulus that is preceded by another, masked stimulus at its location. The first stimulus attracts attention which accelerates perception of the second stimulus. This facilitation arises even if the first stimulus is visually backward-masked by the second one. The paper summarises research on temporal and spatial properties of PLP and the question whether intentions mediate shifts of attention to external events. Possible sources of PLP besides visuo-spatial attention are discussed. Finally, I give a review of feedforward and reentrant models of PLP and compare them to the empirical evidence. (PsycINFO Database Record (c) 2016 APA, all rights reserved)
Keywords: perceptual latency priming; attentional facilitation; visuospatial attention; visual backward masking; prior entry; Attention; Humans; Judgment; Reaction Time; Space Perception; Attention; Priming; Response Latency; Visual Masking; Visuospatial Ability